A transient coupled model of a variable speed transcritical CO2 direct expansion ground source heat pump for space heating and cooling. (September 2019) - Nguyen, A.; Eslami-Nejad, P.
Abstract: A transient coupled model for a variable speed CO2 direct expansion ground source heat pump (DX-GSHP) is developed. An annual simulation for integrated space heating and cooling of a small residential building located in a Canadian climate is conducted, during which numerous operation parameters are evaluated. The model includes a control strategy that regulates pressures of the fluid, thereby allowing the compression cycle to go from subcritical to transcritical for optimal heat rejection. The model can be used to simulate DX-GSHP systems under various loads and evaluate the effect of dynamic thermal behaviour of the ground on the system performance. The results show that there is a strong thermal short-circuiting within BHE when the system is operating at low mass flow, which hinders the system performance. Highlights: A transient model of a variable speed transcritical CO2 DX-GSHP is proposed. Heat transfer in the ground is modeled with thermal resistances and capacities. An annual simulation for space heating and cooling in cold climate is conducted. The results show a strong thermal short-circuiting within BHE at low mass flow.